Are body image issues affecting our adolescents? A cross-sectional study among college going adolescent girls - Subhashini Ganesan; S L Ravishankar; Sudha Ramalingam (Wolters Kluwer Medknow Publications, 2018)
Background: Body image relates to how people think and feel about their own body. In today's society, with the growing sense of ideal body image, adolescents try to lose or gain body weight to attain that perfect body. Body image perception is still naive, and this research will try to understand these unexplored areas, where there is paucity of body image-related studies. Objectives: The objective of the study is to find out the proportion of girls dissatisfied about body image, and the association of various factors with body image dissatisfaction and to ascertain the weight control behaviors adopted by adolescent college girls. Methodology: A cross-sectional study was done among 1200 college girls in Coimbatore. A semi-structured questionnaire was used to collect data on various factors associated with body image dissatisfaction. Body mass index (BMI) of the participants was calculated. Results: Body image dissatisfaction was there among 77.6% of the girls. It was found that factors such as higher BMI, sociocultural pressure to be thin and depression were all significantly associated with body image dissatisfaction. The most commonly followed weight control behaviors were eating small meals and skipping meals. Improving the appearance and body shape were the main reasons for weight control behaviors. Conclusion: This study establishes the fact that body image dissatisfaction is no longer a western concept and affects Indian adolescent girls to a great extent. Hence, effective interventions have to be planned to increase awareness on ideal body weight and protect our young generation from pressures of negative body image.